Compression experiments on marine ice from Nansen Ice Shelf, Antarctica: implications for ice-shelf/continent interactions - Samyn, Denis; Remy, Jean-Philippe; Duval, Paul; Montagnat, Maurine; Tison, Jean-Louis (2007)
info:eu-repo/semantics/published